2017
DOI: 10.1016/j.ejphar.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine and lactation exposure to fluoxetine blunted in the offspring the aortic adaptive response induced by acute restraint stress

Abstract: Selective serotonin reuptake inhibitors are the most widely prescribed antidepressants to women during pregnancy. Maternal treatment with fluoxetine can expose fetuses and neonates to higher levels of serotonin that plays a role in stress response. Thus, the aim of the study was to evaluate whether maternal treatment with fluoxetine interferes with aorta reactivity of adult male offspring after acute restraint stress. Wistar rats were gavaged with fluoxetine (5mg/kg/day) or water (control) during pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Mental stress can induce NOX activation in the endothelium of thoracic aorta [ 63 ] and increase the expression of NOX-4 in carotid [ 64 , 65 ]. This study shows the NOX activation in the brain vessels and the expression of NOX subunits in mRNA and protein levels upon mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mental stress can induce NOX activation in the endothelium of thoracic aorta [ 63 ] and increase the expression of NOX-4 in carotid [ 64 , 65 ]. This study shows the NOX activation in the brain vessels and the expression of NOX subunits in mRNA and protein levels upon mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrent evidence found that maternal exposure to antidepressants brought side effects in aorta reactivity and nitric oxide metabolites. Marques et al (2017 ) confirmed that prenatal fluoxetine exposure blunted the aortic adaptive response in the offspring, indicating a reduction in aortic contraction in the aorta. Previous research has drawn a close relationship between maternal depression and offspring’s high risk of cardiovascular diseases.…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 64%
“…These results suggest that, although fluoxetine may improve endothelial function, other endothelial-independent mechanisms such as nNOS or vasoconstrictor agents may oppose these beneficial effects. To that end, intrauterine exposure of Wistar rats to fluoxetine suppressed the ex vivo aortic hypo-contraction response to stress in offspring [ 35 ]. However, as the authors acknowledged, it is unlikely that the observed reduction in vascular relaxation by fluoxetine was due to endothelial dysfunction because the aortic responses to acetylcholine and phenylephrine were preserved when compared with that in the controls.…”
Section: The Effect Of Antidepressant Treatment On Arteriosclerotic Processes: Experimental Datamentioning
confidence: 99%